THE ROMANTIC GENERAL PANTHEON OF THE CITY OF LIMA DURING THE 19TH CENTURY - Barentzen Gamarra, Hilda (2006)
What is nowadays the Cemetery Priest Maestro is a showcase of theinfluences inherited from the Westem Culture that started with theIllustration and neoclassicism ideas of the late 18th century and continuedup to the 19th century and were consolidated into the romanticism whichtook shape and personality at the end of that century due to the idealisticideologies ofthat period.